2022
DOI: 10.3389/fpsyg.2022.895117
|View full text |Cite
|
Sign up to set email alerts
|

Medical English anxiety patterns among medical students in Sichuan, China

Abstract: This study adapts a Medical English Language Anxiety Scale (MELAS) based on Horwitz’s Foreign Language Classroom Anxiety Scale (FLCAS) and examines students’ anxiety in medical English vocabulary, listening and speaking, communication, literature reading, and academic paper writing. The biographical factors related to medical English language anxiety (MELA) were also tested. The questionnaire sets including five dimensions were distributed to the students from a medical university in Sichuan, China, and were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Deng and Zhou explored medical students’ medical English anxiety in Sichuan, China. They found that 85.2% of the students surveyed suffered moderate above medical English anxiety [ 22 ]. In the questionnaire, 88.89% of the fifth-year pediatric students believed that limited English was one of the most important barriers for scientific research.…”
Section: Discussionmentioning
confidence: 99%
“…Deng and Zhou explored medical students’ medical English anxiety in Sichuan, China. They found that 85.2% of the students surveyed suffered moderate above medical English anxiety [ 22 ]. In the questionnaire, 88.89% of the fifth-year pediatric students believed that limited English was one of the most important barriers for scientific research.…”
Section: Discussionmentioning
confidence: 99%
“…Wang (2015) put forward five strategies to alleviate rural high students' English learning anxiety through qualitative analysis. Deng et al (2022) examined students' anxiety in medical English vocabulary, listening and speaking, communication, literature reading, and academic paper writing, and found the anxiety of rural medical students in each dimension was higher than that of urban medical students.…”
Section: Research On English Learning Anxiety Of Chinese Rural Studentsmentioning
confidence: 99%
“…The need for high levels of English proficiency is particularly pronounced among medical students in the Chinese context. Previous studies have indicated that medical students must possess adequate English proficiency to navigate scientific journals, to stay updated with global medical advancements, and to publish their own empirical work in prestigious journals indexed by the Science Citation Index (SCI) (Li & Heron, 2021;Deng et al, 2022). Moreover, English proficiency has gained significant weight in the selection process for graduate school admissions in China, evident through the inclusion of an English testing segment in graduate school application procedures, such as the Postgraduate Admission Test and graduate school interviews.…”
Section: Introductionmentioning
confidence: 99%